2020
DOI: 10.3390/brainsci10080515
|View full text |Cite
|
Sign up to set email alerts
|

Functional Network Mapping Reveals State-Dependent Response to IGF1 Treatment in Rett Syndrome

Abstract: Rett Syndrome (RTT) is a neurodevelopmental disorder associated with mutations in the gene MeCP2, which is involved in the development and function of cortical networks. The clinical presentation of RTT is generally severe and includes developmental regression and marked neurologic impairment. Insulin-Like growth factor 1 (IGF1) ameliorates RTT-relevant phenotypes in animal models and improves some clinical manifestations in early human trials. However, it remains unclear whether IGF1 treatment has an impact o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 56 publications
1
5
0
Order By: Relevance
“…Nonetheless, IGF-1, BDNF, and apnoea-related genes were also differential at later time points suggesting continuous action of IGF-1 on target pathways. This molecular dynamics resembles the effects of mecasermin on brain activity in participants with RTT, as previously reported by us ( Keogh et al, 2020 ). The reason for the MSR group’s greater changes in gene expression, in response to mecasermin, is unknown and deserves further examination since these molecular changes may disclose key events associated with response to IGF-1 and related compounds.…”
Section: Discussionsupporting
confidence: 87%
“…Nonetheless, IGF-1, BDNF, and apnoea-related genes were also differential at later time points suggesting continuous action of IGF-1 on target pathways. This molecular dynamics resembles the effects of mecasermin on brain activity in participants with RTT, as previously reported by us ( Keogh et al, 2020 ). The reason for the MSR group’s greater changes in gene expression, in response to mecasermin, is unknown and deserves further examination since these molecular changes may disclose key events associated with response to IGF-1 and related compounds.…”
Section: Discussionsupporting
confidence: 87%
“…It implied that insulin or insulin-like factor pathways might play an important role in the pathogenesis of RTT or RTT-like syndrome. It has been reported that IGF1 could ameliorate RTT-relevant phenotypes in animal models and improve some clinical manifestations in clinical trials (Pini et al, 2012 ; Keogh et al, 2020 ). Since possessing the ability to bind and regulate the expression of IGF1R, it is very likely that PRKD1 is a novel contributor to the clinical phenotypes of FOXG1-related disorder.…”
Section: Discussionmentioning
confidence: 99%
“…[84][85][86] Glatiramer acetate has also demonstrated reduction in EEG abnormalities (eg, decreased epileptiform discharges). 87 Finally, Keogh et al 88 investigated the impact of IGF1 on network formation in responders in comparison to nonresponders based on clinical assessments. There was a significant difference in network measures that was predicted with 100% accuracy using a machine learning model applied to pretreatment data and highlighted the promise that quantitative EEG analysis has a role as a biomarker in clinical trials.…”
Section: Rett Syndromementioning
confidence: 99%
“…There was a significant difference in network measures that was predicted with 100% accuracy using a machine learning model applied to pretreatment data and highlighted the promise that quantitative EEG analysis has a role as a biomarker in clinical trials. 88 Rett syndrome may also be a candidate for gene replacement therapy as even postnatal rescue of the genotype demonstrates rescue of the behavioral, motor, and EEG phenotype. 89…”
Section: Rett Syndromementioning
confidence: 99%